Antifungal activity of ethanolic Psidium guajava L. leaf extract against food spoilage fungi - Nursanty, R.; Padzil, K. N. M.; Mahyudin, N. A.; Jaafar, A. H.; Rukayadi, Y. (Malaysian Journal of Microbiology, 2025)
Abstract not available.